Deteksi dan Pencegahan Serangan Wormhole pada Protokol Routing AOMDV menggunakan Gabungan Metode Delphi dan RTT-TC pada Jaringan MANET - Nini Kurnia Safitri; Andy Hidayat Jatmika; Moh. Ali Albar (Informatics Engineering Dept., Faculty of Engineering, University of Mataram, 2019)
Mobile Ad Hoc Network (MANET) is a network consisting of a group of mobile nodes that don't have a fixed infrastructure. This causes the MANET to be vulnerable to attacks that can interfere with the process of communication and data transmission on the network. One type of attack that can attack the MANET is a wormhole attack. The wormhole is an attack on a network where there are two or more wormhole nodes that are interconnected and work together to attack network traffic or discard data packets it receives. Each wormhole node will be connected to each other using a wormhole link. To prevent wormhole attacks, the method that can be used is the Delay Per Hop Indicator (Delphi) method and the Round Trip Time and Topological Comparison (RTT-TC) method. The Delphi detects wormhole attacks by calculating the delay in each hop from the source node to the destination node. Whereas in the RTT-TC, wormhole attacks are detected by calculating the value of round trip time and topological comparison. The Delphi and RTT-TC methods have their advantages and disadvantages. In this study, it was proposed to combine the Delphi and RTT-TC methods to cover the disadvantage of each method.